Pain Is Associated with Recurrent Falls in Community‐Dwelling Older Adults: Evidence from a Systematic Review and Meta‐Analysis. Issue 7 (16th May 2014) - Stubbs, Brendon; Schofield, Pat; Binnekade, Tarik; Patchay, Sandhi; Sepehry, Amir; Eggermont, Laura
Abstract Background Pain and recurrent falls are highly problematic in community‐dwelling older adults, yet the association remains elusive. Objective The objective of this study was to investigate the association between pain and recurrent falls in community‐dwelling older adults. Design Two independent reviewers conducted searches of major electronic databases, completed methodological assessment, and extracted the data of all included articles. Articles that were included are those that 1) involved community‐dwelling older adults; 2) recorded recurrent falls; and 3) assessed pain. Articles that were excluded are those that included participants with dementia, any neurological conditions, or those with orthopedic trauma/surgery in the past 6 months. Results Out of a potential of 71 articles, 11 met the inclusion criteria and 7 (N = 9, 581) were eligible for the meta‐analysis. The annual prevalence of recurrent falls in those reporting pain (12.9%) was higher than the pain‐free control group (7.2%, P < 0.001). A global meta‐analysis established that pain was associated with recurrent falls (odds ratio [OR]: 2.04, confidence interval [CI]: 1.75–2.39; N = 3, 950 with pain and N = 5, 631 controls), and this was decreased in a subgroup meta‐analysis utilizing prospective studies only (OR: 1.79, CI: 1.44–2.21, P < 0.001, I2 = 0%; N = 3, N = 2, 646). A subgroup analysis comparing recurrent fallers vs non‐fallers only (OR: 2.18, CI: 1.82–2.60, N = 6, 320, I2 = 0%) established the odds were particularly higher than single fallers vs non‐fallers (OR:1.44, CI: 1.26–1.64, N = 6, 903, I2 = 0%). Conclusion Older adults with pain are at particularly increased risk of recurrent falls. Clinicians working with recurrent fallers should routinely assess pain while pain specialists should inquire about older adults' falls history.